Photocatalytic Performance of Carbon Monolith/TiO2 Composite - Marina Maletić; Marija Vukčević; Ana Kalijadis; Zoran Laušević; Mila Laušević (Advances in Materials Science and Engineering)
The new and simple approach for deposition of catalytically active TiO2 coating on carbon monolith (CM) carrier was presented. CM photocatalysts were impregnated with TiO2 using titanium solution and thermal treatment, and their photocatalytic activity was investigated in the process of methylene blue (MB) photodegradation. For the purpose of comparison, CM composite photocatalysts were prepared by dip-coating method, which implies binder usage. The presence of TiO2 on CM carrier was confirmed by Raman spectroscopy and scanning electron microscopy. The sorption characteristics of CM and the role of adsorption in the overall process of MB removal were evaluated through amount of surface oxygen groups obtained by temperature-programmed desorption and specific surface area determined by BET method. CM has shown good adsorption properties toward MB due to high amount of surface oxygen groups and relatively high specific surface area. It was concluded that photocatalytic activity increases with CM disc thickness due to increase of MB adsorption and amount of deposited TiO2. Good photocatalytic activity achieved for samples obtained by thermal treatment is the result of better accessibility of MB solution to the TiO2 particles induced by binder absence.